2019
DOI: 10.1177/0165551518819970
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the information needs and information access channels of farmers: An empirical study in Guangdong, China

Abstract: Information plays an important role in meeting the quantitative and qualitative goals of agriculture in the 21st century. As an emerging economy in a developing continent, China has already made many interventions to use information technology to support agricultural development. However, information service in some rural areas is still severely limited. The overall impact of the changing information environment on the farmers’ information needs and access channels has not been fully studied. Thus, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The insignificance of age to the use of radio could likely be that farmers have other means of receiving information such as peer groups, friends, relatives and neighbours. The result is in line with the empirical evidence found in the work of (Chen et al, 2020) that older farmers' accorded much priority to agricultural market information received from their colleagues, at the expense of other production information. In addition, the sex of the respondents' portrayed a significant association (X 2 = 14.049, df=5) with the utilization of radio.…”
Section: Influence Of Farmers' Place Of Residence Sex Age Income and ...supporting
confidence: 88%
“…The insignificance of age to the use of radio could likely be that farmers have other means of receiving information such as peer groups, friends, relatives and neighbours. The result is in line with the empirical evidence found in the work of (Chen et al, 2020) that older farmers' accorded much priority to agricultural market information received from their colleagues, at the expense of other production information. In addition, the sex of the respondents' portrayed a significant association (X 2 = 14.049, df=5) with the utilization of radio.…”
Section: Influence Of Farmers' Place Of Residence Sex Age Income and ...supporting
confidence: 88%
“…These factors mean that the lower the KEB, the higher the PU and PEU. Information plays an essential role in agricultural economic development (Chen and Lu, 2019) and human decision-making (Raghunathan, 1999). Access to formal information affects farmers' perceptions, leading to technology adoption behavior (Lambrecht et al, 2014).…”
Section: The Barriers To Adoption Of Ecesmentioning
confidence: 99%
“…Various studies have reported the effect of different factors on information-seeking behaviour (Azadeh and Ghasemi, 2015;Brhane et al, 2017;Chen and Lu, 2019;Ochei-Idiake et al, 2016;Waqas, Khan, Nosheen and Ahmad, 2015). Chen and Lu (2019) outlined how individual, social and family characteristics influenced information needs and access channel preferences. Brhane et al (2017) also reported that information seeking behaviour was affected by a variety of factors ranging from geographic location, economic status, to demographic characteristics, psychological and institutional factors.…”
Section: Factors Influencing Information-seeking Behaviourmentioning
confidence: 99%